Growth and characterization of GaN-based quantum cascade laser (QCL) structures - Yuen, Ho Ching (Nanyang Technological University, 2021)
This report presents the studies completed by the author during his final year project with Temasek Laboratories @ NTU. The project focuses on the simulation of AlGaN/GaN-based Quantum Cascade Lasers (QCL) on polar and non-polar planes and the growth, optimization, and characterisation of GaN-based structures. The simulation works were carried out using Nextnano, a software for simulating electronics and optoelectronic semiconductor devices. The work aimed to investigate the gain parameters of GaN-based QCLs and to study the effects that different crystal orientations of GaN on the behaviour and performance of QCL. It was observed that gain for polar condition GaN is lower than non-polar condition GaN. Additionally, the characterization of GaN-based structures was carried out. Analysis was done using optical microscopy, atomic force microscopy, hall measurement system, and high-resolution X-ray diffraction. Growth of GaN-based structures were performed by research staff in Prof. Radha’s lab. GaN layers with silicon doping were characterized. With and without Si doping, no change in the surface morphology was observed. Hall measurement was conducted on silicon doped GaN layers and achieved a bulk carrier concentration of 5.39×1018 −3. AlGaN/GaN structure was also characterized, achieving close to desired thicknesses for the quantum wells.